ANALYSIS OF THE READINESS OF MINISTRY OF RELIGIOUS AFFAIRS EMPLOYEES ON THE ISSUE OF IKN NUSANTARA RELOCATION IN THREE PTKIN - Muhammad Fanshoby; Tantan Hermansah; Nofia Natasari (FAKULTAS DAKWAH UIN SALATIGA, 2023)
The urgency of relocating the national capital to IKN Nusantara is rooted in its symbolic representation of the nation's identity. The capital's significance is sensitive, serving as a cornerstone of national symbols and unity. The Ministry of Religious Affairs (Kemenag) is at the forefront of promoting national unity through its campaign on religious moderation, essential for IKN Nusantara's development. State Islamic Religious Universities (PTKIN), under Kemenag, lead in studying religious moderation. PTKIN's pivotal role in strengthening national unity aligns with IKN Nusantara's objectives. This study aims to assess the readiness of PTKIN employees towards IKN Nusantara within the Ministry of Religious Affairs. Using a quantitative survey approach, data from 95 PTKIN employees in UIN Syarif Hidayatullah Jakarta, UIN Sunan Gunung Djati Bandung, and UIN Sultan Maulana Hasanudin Banten were analyzed. Results indicate UIN Jakarta, followed by UIN Banten and UIN Bandung, as most prepared for the move. Readiness also varies with age, service duration, and gender, with male employees showing higher readiness to relocate to IKN.